Depletion of PAK1 enhances Ubiquitin-mediated Survivin degradation in pancreatic β-cells - Chen, Yi-Chun (Landes Bioscience, 2013)
Functional β-cell mass deficiency in diabetes results from imbalanced β-cell death and replication, and decreased PAK1 protein levels in human islets from donors with type 2 diabetes implicates a possible role for PAK1 in maintaining β-cell mass. Here, we aim to address the linkage between PAK1 and Survivin, a protein essential for β-cell replication. PAK1 knockout (KO) mouse islets exhibited decreased expression of Survivin protein. MIN6 β-cells with siRNA-mediated suppression of PAK1 also had decreased Survivin protein and exhibited an increased level of ubiquitinated-Survivin. However, no significant changes in Survivin mRNA were found in islets from PAK1 KO mice and PAK1-depleted MIN6 β-cells. The decreased Survivin level in MIN6 cells subjected to hyperglycemic stress was prevented by expression of exogenous PAK1. Moreover, overexpressing Survivin restored proliferation of β-cells that was impaired by the loss of PAK1. These data implicate a role for PAK1 in regulating Survivin protein stability in the β-cell and suggest PAK1 as a potential molecular target for the restoration of β-cell mass.